The Issue of Acceptability of the Online Education - Sandru, Adriana-Maria (Didactica Danubiensis, 2024)
The article identifies the state's obligations regarding online education, taking into account the essential features of traditional education, established within the UN, namely "availability", "accessibility", "acceptability" and "adaptability". It addresses the acceptability of the online education by approaching aspects such as online assessment and interaction between students and between students and teachers as perceived by students. Il also gives an insight into the legal framework adopted to make education acceptable.